Complementarity Between The Industries In The Pandamaran Industrial Estate And The Seaport Of Port Klang. - Kumarasamy, Nyanasaigran (Pusat Pengajian Ilmu Kemanusiaan, 1982)
Industrial estates are planned areas of industrial concentration which are often used as an effective device in accelerating industrial and economic development of a region. This study is aimed at investigating the extent of complemen tarity between the industries in the Pandamaran Industrial Estate the seaport of Port Klang.